A role-based perspective on leadership as a network of relationships - Sheard, A. G.; Kakabadse, Andrew P. (Emerald Group Publishing Limited, 2007)
The research described in this article seeks to address the question of the extent to which a role-based perspective can provide insight into the distributed and networked form of leadership.
Keywords: Leadership; Organizational structures; Social networks